(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Uveitis is a cause of blindness in about 10% of cases. According to many studies, TNF-? plays an important role in the development of uveitis. Anti-TNF-? are widely used in rheumatology and recently in ophthalmology. We carried out the analysis of literature on the use of anti-TNF-?. Large studies have been carried out and good results of anti-TNF-? usage in uveitis associated with JIA, Behcet’s disease, ankylosing spondylarthropathies, sarcoidosis have been obtained. The profile of side effects and safety anti-TNF-? is quite acceptable for use in clinical practice. It is highly important that anti-TNF-? has a corticosteroid preserving effect which reduces side-effects associated with treatment, at this time has high efficacy of therapy.